2020
DOI: 10.1017/s1751731119002726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin administration to lactating cashmere goats on milk production of dams and on hair follicle development in their offspring

Abstract: Melatonin treatment in adult cashmere goats can increase cashmere yield and improve cashmere fibre quality by inducing cashmere growth during cashmere non-growth period, of which time cashmere goats are in the mid and late stages of lactation. However, whether melatonin treatment in adult cashmere goats affects their offspring’s growth performance remains unknown. Therefore, the objectives of the current study were to determine the effects of melatonin treatment in adult cashmere goats on cashmere and milk pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Moreover, the role of melatonin in promoting Cashmere yield has been demonstrated for decades [ 71 ], and melatonin also participates in stem cell differentiation pathways. Melatonin induces Cashmere growth through melatonin receptors [ 72 ] and is a critical intermediary between photoperiod and Cashmere growth [ 73 ]. Cashmere goats breed seasonally, and usually give birth between March and April, which conforms to a spring kidding system [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the role of melatonin in promoting Cashmere yield has been demonstrated for decades [ 71 ], and melatonin also participates in stem cell differentiation pathways. Melatonin induces Cashmere growth through melatonin receptors [ 72 ] and is a critical intermediary between photoperiod and Cashmere growth [ 73 ]. Cashmere goats breed seasonally, and usually give birth between March and April, which conforms to a spring kidding system [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin induces Cashmere growth through melatonin receptors [ 72 ] and is a critical intermediary between photoperiod and Cashmere growth [ 73 ]. Cashmere goats breed seasonally, and usually give birth between March and April, which conforms to a spring kidding system [ 72 ]. Melatonin is administered to Cashmere goats in April, because melatonin treatment in adult Cashmere goats during the Cashmere non-growth period has been found to induce Cashmere growth, increase Cashmere yield, improve Cashmere quality and decrease the fiber diameter [ 74 ], which also present similar results from other countries of the world [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effects of melatonin on the hair follicle have been repeatedly described, e.g., in cashmere goats [77] and rabbits [78], but the interest was mostly focused on hair growth and not so much on differentiation. In the Cashmere goat, a seasonal breeder that produces a valuable fur, the influence of melatonin on hair growth is likely, from a fundamental point of view, as it is related to the formation of winter fur.…”
Section: Hair Follicle Stem Cells: a Lesson On Dose Conditionality An...mentioning
confidence: 99%
“…It was reported that MT can accelerate the hair follicle reconstruction process and induce secondary hair follicle development, which results in early entry into the next cashmere growth cycle and increases cashmere yields (Duan et al, 2017;Ge and Wang, 2018;Yang X. Z., 2020;Yang C. H., 2020). According to previous studies, two MT implants during the non-fleece period can improve the cashmere yields of Inner Mongolia cashmere goats to different degrees (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%